Optimal model of the concept of radio-relay equipment maintenance - Radonjić, Vojkan M.; Jovanović, Danko M.; Ćirić, Milenko P. (Vojnotehnički glasnik / Military Technical Courier, 2013)
This paper presents the results of applying the optimal model of the concept of maintenance of modern radio-relay equipment (RRE). ﻿The model, is based on condition based preventive maintenancewith the control of the level of reliability, and uses a number of positive structural and technological capabilities of the machine in order to decrease overall maintenance costswhile maintaning the achieved level of the required device reliability. Introduction The aim of this paper is to review the maintenance models, with an emphasis on preventive maintenance, in order to identify the best RRE model maintenance and set up a proper maintenance organization. ﻿For the application of a model of maintenance, one must be familiar with construction-technological features and capabilities of the device which provide its reliability and maintainability. ﻿The ultimate goal of this research is to choose and establish an optimal maintenance model which will enable controlled monitoring of device reliability in order to fully utilize resources. Types of Preventive Maintenance Two types of preventive maintenance have been presented including: traditional planned maintenance and condition based maintenance. ﻿Condition based maintenance is a type of preventive maintenance based on a periodic or continuous control of devices in use. ﻿Based on the results of the control, decisions are made on the necessary time and extent of planned activities. Condition based maintenance, due to constant control during operation, allows full utilization of device modulecomponents , which makes it optimal compared to traditional preventive maintenance. Methods of condition based maintenance. There are two types of condition based maintenance: one with the parameter control and the other with the reliability control.The choice of an appropriate method is done based on the algorithm in Figure 3. ﻿Considering the requirements that must be met when choosing the model of condition based maintenance and the algorithm for model selection, a model of condition based maintenance is chosen with the control of the device reliability and component modules. ﻿The fact that the intensity of the failure of devices and modules is constant over the life of the device is a critical factor in choosing a model of condition based maintenance which will be used in further research. ﻿The model will enable the optimal maintenance of devices with maximum reliability and minimum maintenance costs. Condition based maintenance with the control of the level of reliability In models of condition based maintenance with the control of the level of reliability, a reliability level is a criterion of technical condition and expressed by reliability. ﻿The indication of the reliabilityis the parameter – failure intensity. ﻿In applying the model, there is another parameter used- allowed reliability level. ﻿The permitted level of reliability is calculated for each component separately and for the entire device. ﻿In this maintenance model, during the lifetime of the device, the actual level of reliability is constantly compared with the allowed value of the reliability of the device or module, as shown in the algorithm in Figure 4. The application of this maintenance model requires constant collection of operational data about the reliability of devices and modules during their lifetime. RRE characteristics from the aspect of the maintenance model In the selection phase of the maintenance model, it is stated that RRE must meet certain requirements such as: unit design is characterized by a high degree of technologicality and is based on the serial modular principle; the device operates within the mobile system in which the operation of the device is controlled by a computer system, and the device is pre-tested for the defectafion of device correctness. ﻿From the technological point of view, it was assumed that there is equipment for all levels of maintenance, trained personnel, and required technological procedures for all levels of maintenance. The application of the condition based maintenance with the control of the level of reliability and the results of the application In accordance with the defined assumptions,the maintenance model was applied. ﻿The RRE operation is controlled within the mobile system,using a compute with, appropriate software. . ﻿The communication ofthe computer with RREgives all the relevant information about the unit. ﻿A part of the maintenance data is entered manually into the appropriate application software. ﻿Based on the collected data, the computer calculates all relevant parameters for the implementation of the model maintenance, numerically and graphically. ﻿Figure 7 shows the algorithm of the optimal model of condition based maintenance of RRE with the control of the reliability level. ﻿The results of applying the optimal maintenance model are also shown. Based on the activities during the research and on the application of the maintenance model, it can be seen that the highest maintenance costs are directed to the replacement of component modules. ﻿The optimality of the condition based maintenance model allows the use of modules after the expiry of resources, or up to failure,without disrupting the functions of the device. Conclusion The conducted research shows that the assumed RRE maintenance model provides quality and cost-effective RRE maintenance of the latest generation with the use of existing resources and RRS units in which they are incorporated. ﻿The research also shows that the assumed model of condition based maintenance with the control of the level of reliability enables: - full use of structural and technological characteristics of the device as a function of efficient and cost-effective equipment maintenance, - better planning of preventive maintenance, - involvement of personnel and experts from the lowest level of maintenance and professional raising of the basic maintenance level, - availability of information on resources, equipment and maintenance, to higher levels of maintenance and decision-making structures, - uniform and organized data collection from service and device life and RRS, - reduction of maintenance costs to a minimum, - changing the constituent moduleswith the highest maintenance costs, upon failure and not upon the expiry of resources, provided that the module performs its functional purpose and does not violate the reliability of the device, - an option of applying the maintenance model to other devices in RRS.